Transient vascular occlusions in a zebrafish model of mycobacterial brain infection - Megan I. Hayes; Sumedha Ravishankar; Tariq Qayum; Victor Nizet; Cressida A. Madigan (PLoS ONE, 2025)
Mycobacterial brain infection, for example tuberculous meningitis (TBM), caused by Mycobacterium tuberculosis, is a severe manifestation of tuberculosis that occurs when the bacteria invade the brain. In addition to extensive inflammation, vascular complications such as stroke frequently arise, significantly increasing the risk of disability and death. However, the mechanisms underlying these vascular complications remain poorly understood, as current knowledge is derived exclusively from human studies. To date, no animal model has been established to investigate the onset and progression of vascular pathology in TBM. Here, we use transparent zebrafish larvae to investigate vascular pathology during the early stages of TBM, establishing a model for studying vascular complications from mycobacterial brain infection. We find that mycobacteria preferentially attach to the lumen of vessel bifurcations and induce vessel enlargement. These attached microcolonies are sufficient to occlude brain blood vessels in the absence of an organized thrombus. The majority of microcolony-associated occlusions are transient and contribute to global hypoperfusion of the brain. These vascular disruptions lead to accumulation of oxidative stress and cell death in both the vasculature and neurons. Taken together, these findings demonstrate the occurrence of ischemic events during the early stages of mycobacterial brain infection and establish an animal model for studying vascular complications in TBM.